Shear bond strengths of buccal tubes - Purmal, K.; Sukumaran, P. (Australian Society of Orthodontists, 2010)
Aims: To investigate the shear bond strengths of buccal tubes and to determine the sites of failure. Method: Four orthodontic buccal tubes were selected: A, American Orthodontics; B, 3M Unitek - small base; C, 3M Unitek large base; D, Hangzhou Dentop. Twenty buccal tubes from each group were bonded to the buccal surfaces of lower right first molars with the some light-cured composite resin. The buccal tubes were debonded with a universal testing machine and the data analysed. The amount of adhesive remaining on the teeth after debonding was classified with the modified adhesive remnant index (ARI). Results: The groups ranked from the highest to lowest bond strength (MPa) were: B, A, D and C. The bond strengths of the buccal tubes, except Groups A and B, were significantly different (p < 0.05). The majority of the buccal tubes 163 per cent) had modified ARI scores of 1 and 2 and 25 per cent of the tubes had scores of 4 and 5. After debonding, no adhesive remained on 40 per cent of the teeth in Groups B and D. Conclusions: The shear bond strengths of the buccal tubes fell below the value considered to be clinically acceptable. There were no differences between the shear bond strengths of the buccal tubes with photoetched and microetched bases. The buccal tubes with the largest base failed prematurely, possibly because the unsupported bonding pad flexed during debonding. (Aust Orthod J 2010; 26: 184-188)